2014
DOI: 10.2139/ssrn.2558908
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal Policy and Inclusive Growth in Advanced Countries: Their Experience and Implications for Asia

Abstract: Advanced economies have a significantly longer history of using fiscal policy to tackle inequality and promote inclusive growth than those in developing Asia. Therefore, as developing Asia explores the more active use of fiscal policy for inclusive purposes, it can learn from the experiences of advanced countries. Those experiences clearly suggest that fiscal policy can have a significant effect on inequality which provides some cause for optimism about its equity-promoting potential. Nevertheless, that optimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 19 publications
0
15
0
1
Order By: Relevance
“…Studi terdahulu yang membahas kebijakan fiskal dan implikasinya terhadap pertumbuhan inklusif menggunakan benchmarking study. Heshmati et al (2014) misalnya, menggunakan negara anggota OECD sebagai benchmark guna memberikan rekomendasi kebijakan fiskal yang relevan dalam mempromosikan pertumbuhan inklusif di negara Asia. Hasilnya, bantuan pemerintah kepada kaum miskin dan rentan dapat menjadi alat yang efektif untuk mencapai pertumbuhan inklusif di Asia.…”
Section: Studi Terdahuluunclassified
“…Studi terdahulu yang membahas kebijakan fiskal dan implikasinya terhadap pertumbuhan inklusif menggunakan benchmarking study. Heshmati et al (2014) misalnya, menggunakan negara anggota OECD sebagai benchmark guna memberikan rekomendasi kebijakan fiskal yang relevan dalam mempromosikan pertumbuhan inklusif di negara Asia. Hasilnya, bantuan pemerintah kepada kaum miskin dan rentan dapat menjadi alat yang efektif untuk mencapai pertumbuhan inklusif di Asia.…”
Section: Studi Terdahuluunclassified
“…In addition to this, innovative approaches, such as the greater use of taxes on property and energy (such as carbon taxes) could also be considered for both advanced and developing economies (International Monetary Fund IMF). The impact that such measures can have on income inequality and GDP growth are mixed, as Heshmati et al (2015) showed in their summary of the effects of different fiscal policy measures (see Table 1). Among fiscal policy options, Bastagli et al (2012) showed that direct income taxes and transfers had a 15% decrease on the Gini index for 25 OECD member countries during the 1985-2005 period.…”
Section: Summary Of Fiscal Policymentioning
confidence: 99%
“…These include, among others: (i) reductions in class sizes, (ii) additional financial and learning support for teachers and students in lower socio-economic areas, (iii) provisions for free nursery schooling, (iv) a renewed emphasis on vocational education, (v) better access to tertiary education loan and grant schemes for lower-income families, and (vi) the offering of provisional spaces for ethnic minorities within certain degree level programs. Such programs are funded through increases in fiscal spending in the education sector through a range of tax policy initiatives, which are detailed above in Table 1 (see Heshmati et al 2015).…”
Section: Educationmentioning
confidence: 99%
“…In fact, in the advanced economies, redistribution of income via progressive taxation and pro-poor public spending has long been one of the main objectives of fiscal policy. [see Heshmati, Kim, and Park (2014)] A number of studies confirm that fiscal policy had a significant pro-equity impact in advanced economies. Bastagli et al (2012) found that, on average, 25 OECD countries experienced a 15% decrease in the Gini index of inequality due to taxes and transfers in 1985-2005.…”
Section: Literature Reviewmentioning
confidence: 99%